1994
DOI: 10.1139/x94-281
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Douglas-fir beetle infestation of high-risk stands by antiaggregation and aggregation pheromones

Abstract: A combination of antiaggregation and aggregation pheromones was tested for protecting stands of Douglas-fir (Pseudotsugamenziesii (Mirb.) Franco) at high risk for infestation by the Douglas-fir beetle (Dendroctonuspseudotsugae Hopkins). The antiaggregation pheromone, 3-methylcyclohex-2-en-1-one (MCH), was applied in a bubble capsule formulation to the perimeter of 1-ha circular plots at a rate of 60 g/plot. Treated plots also had three or four clusters of four Lindgren funnel traps baited with frontalin, seude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Endemic populations are important contributors to ecosystem processes (Edmonds and Eglitis, 1989), but epidemic populations often cause serious economic losses to a variety of resource values. While several management alternatives exist for DFB populations (Schmitz and Gibson, 1996;Ross and Daterman, 1994, 1995, 1997Dodds et al, 2000;Ross et al, 2001), a better understanding of the temporal and spatial patterns of DFB infestations may increase the effectiveness of these management techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Endemic populations are important contributors to ecosystem processes (Edmonds and Eglitis, 1989), but epidemic populations often cause serious economic losses to a variety of resource values. While several management alternatives exist for DFB populations (Schmitz and Gibson, 1996;Ross and Daterman, 1994, 1995, 1997Dodds et al, 2000;Ross et al, 2001), a better understanding of the temporal and spatial patterns of DFB infestations may increase the effectiveness of these management techniques.…”
Section: Discussionmentioning
confidence: 99%
“…with baited traps surrounding the area treated with anti-aggregants. Indeed, Ross and Daterman (1994) found that treating with MCH-releasing bubblecaps concentrated D. pseudotsugae attack onto trees within a limited area outside the treated stand, so it would be wise to test the combined approach in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have explored the role of aggregation pheromones and host volatiles in the colonization of host trees, the role of anti-aggregation pheromones and nonhost volatiles in regulation of attack rates, density and within-tree spacing and the use of kairomones by natural enemies and competitors in prey location and host finding. These have led to advances in bark beetle management through the forecasting of infestation trends ( Billings, 1988 ), the development of containment methods ( Borden et al , 1983;Gray & Borden, 1989 ), stand protec tion and spot suppression ( Gibson et al , 1991;Shea et al , 1992;Shore et al , 1992;Ross & Daterman, 1994Clarke et al , 1999;Progar, 2003 ) and mass trapping efforts ( Räty et al , 1995;Shea & Neustein, 1995 ). Baited traps are commonly used to determine the response of bark beetles to semiochemicals in the field.…”
Section: Introductionmentioning
confidence: 99%